Critical roles of the E3 ubiquitin ligase FBW7 in B‐cell response and the pathogenesis of experimental autoimmune arthritis. Issue 3 (16th August 2021) - Feng, Chunlei; Li, Lingyun; Zhou, Lei; Li, Dali; Liu, Mingyao; Han, Shuhua; Zheng, Biao
Abstract: Proper regulation of B‐cell function is essential for effective humoral immunity and maintenance of immune tolerance. Here, we found that FBW7 (F‐box/WD40 repeat‐containing protein 7) is highly expressed in germinal centre B and B1 cells, and confirmed that it has an intrinsic role in maintaining homeostasis of mature B cells and B‐1 cells. FBW7 deletion led to an impairment of antibody response, and although germinal centre formation was not affected, antibody class‐switch recombination and affinity maturation processes were defective. Likewise, memory immune response was severely impaired. Moreover, FBW7 ablation ameliorated the pathogenesis of an autoimmune disease model, collagen‐induced arthritis, by reducing the production of anti‐collagen II autoantibodies. Taken together, these data suggest that FBW7 may be an attractive target for developing new therapeutics for the treatment of autoimmune diseases. Abstract : FBW7 is essential for B‐cell maintenance and survival. FBW7 deletion impairs antibody class switch recombination and affinity maturation. FBW7 deficiency decreases incidence and disease severity in the CIA model.